(untitled) (Colombia Medica, 2008)
Introduction: Quality of life is a concept that has evolved through time, happening of the well-being to the standard of life, in accordance with the social and cultural conditions of the time; its different definition is vague and adopts several meanings following the perception, context and scale of values, for this reason it takes elements from different disciplines for its conceptualization and can be moderate of general form or through their social, economic, personal components, of health and social security. Objective: To describe the perception on different aspects of life quality among men and women from 20 to 64 y.o., resident in Medellín in 2005, with a design of complex sampling, and the purpose of contributing to the state of the art. Materials and methods: A cross-sectional descriptive population study was designed, with primary source of information constituted by two samples: 659 men and 683 women, who represented 523,705 and 651,704, respectively, according to factors of population expansion; selected with probabilistic complex sampling, stratified by socioeconomic level, cluster sampling. Five people by cluster and only one person by house were considered, to them a survey designed by the investigators was applied, taking as reference generic scales and applied by inquirer personnel hired by Universidad de Antioquia. Results: Adult population valued over 75% personal, social perception, state of health and house conditions; the economic situation reached 39% and the attention in health 64%, the best one described by both sexes was the personal life with 80% and the present quality of life with 77% obtaining a higher valuation among men. Conclusions: Life quality to the adult population of Medellín was explained mainly by personal satisfaction, economic conditions and social security, without significant differences in the general valuation, among men and women.